THE ROLE OF PREDICTOR PLACENTAL GROWTH FACTOR, SOLUBLE ENDOGLIN, SOLUBLE-FMS-LIKE-TYROSINE KINASE-1 AND PULSATIL UTERINA ARTERIAL INDEX TO PREDICT THE EARLY ONSET OF PREECLAMPSIA - LUBIS, MUARA P. (International Journal of Current Pharmaceutical Research, 2020)
Objective: In preeclampsia, there will be an increase in SFlt-1 and in and decrease in PlGF levels. This condition will cause disorders of vasculogenesis and angiogenesis in fetomaternal circulation, which will eventually lead to preeclampsia syndrome such as proteinuria, hypertension and endothelial dysfunction. Methods: An observational study design with nested case-control. The study was conducted at Bunda Thamrin Hospital, Tanjung Mulia Medika Hospital, Sundari Hospital and private practice, from March to November 2018, with a sample of 64 research subjects. Results: The results of this study indicate that there were significant values with p<0.05, namely the pulsatile value of the uterine artery index with a 1.228 cut-off point, Area Under Curve (AUC) of 78.2% (95% CI 59.3%-97%), sensitivity 80%, specificity 64.6%, PlGF level with 441 pg/ml cut-off point, Area Under Curve (AUC) of 82.5% (95% CI 61.5%-100%), sensitivity 80%, specificity 87.7%, sFlt-1 level with a cut-off point of 10087.5 pg/ml, Area Under Curve (AUC) of 81.2% (95% CI 63.6%-98.9%), sensitivity 80%, specificity 67.7% while sEng with p value>0.05 which means it is not significant. Conclusion: From this study, no significant differences were found in sEng, whereas differences were found in the pulsatile value of the uterine artery index, PlGF levels, and sFlt-1 levels in the incidence of early-onset preeclampsia. From the multivariate analysis, an examination of PlGF levels alone is sufficient as a predictor of early-onset preeclampsia.